A mid- to late-Holocene record of vegetation decline and erosion triggered by monsoon weakening and human adaptations in the south-east Indian Peninsula. (December 2017) - Cui, Meng; Wang, Zhanghua; Nageswara Rao, Kakani; Sangode, S J; Saito, Yoshiki; Chen, Ting; Kulkarni, Y R; Naga Kumar, K Ch V; Demudu, G
The mid- to late-Holocene monsoon decline led to aridification of the Indian Peninsula impacting the early agricultural practices in the region. Our analysis of organic carbon, mineral magnetic properties and AMS 14 C dating of a 54.2-m-long sediment core (CY) from the Godavari Delta, India, showed changes in the organic carbon source and sediment provenance, which are linked to the changes in vegetation and soil/rock erosion caused by widespread aridification and associated human adaptation in central India. Our results show a decline in the concentration of ferrimagnetic minerals, indicating reduced input from the basalts of the Deccan Plateau after ~6.0 cal. ka BP in response to the weaker Indian monsoon. δ 13 C values show a distinct increase from ~4.9 cal. ka BP, indicating an increase in C4 plant sources under the continued weak monsoon phase, whereas a higher ferrimagnetic mineral concentration in the sediment suggested an increased Deccan basalt source. Abrupt increase in δ 13 C values and decrease in TOC content accompanied with a significant increase in ferrimagnetic mineral concentration from ~3.2 to 3.1 cal. ka BP reflected a shift of organic carbon and sediment source and a severe decline in vegetation coverage. Such phenomena indicate intensified deforestation and soil/rock erosion in the Deccan Plateau producing higher ferrimagnetic mineral inputs, which is in agreement with significant expansion of agricultural activities in the Deccan Chalcolithic cultural period. In addition, C3 plants recovered and magnetic concentration declined during the wet events (4.6 and 4.0 cal. ka BP) of Neolithic time, while both C3 plants and magnetic parameters increased during the wet events (3.1–2.8 and 2.1 cal. ka BP) of the Chalcolithic cultural period. This implies increased agricultural activity and the onset of human modification of the ecosystem.